A Comparative Assessment Of Ti-47.5 At.%Al Cathodically Modified By Precious Metal Addition - Synopsis - I. A. Mwamba (The Southern African Institute of Mining and Metallurgy, 2013)
Plain and alloyed titanium aluminides of composition Ti-47.5 at.% Al were prepared by melting commercial-purity titanium and aluminium with additions of 1 at.% precious metal. The as-cast alloys were subjected to potentiodynamic scans in 5, 15, and 25 wt% HCl aqueous solutions at room temperature and compared for their abilities to spontaneously passivate. Addition of precious metals resulted in a general improvement of corrosion resistance by increasing the open circuit potential to more noble values. Addition of 1 at.% gold or silver to titanium aluminide did not significantly increase the corrosion potential (Ecorr) above that of the plain titanium aluminide alloy, indicating that gold and silver are not sufficient cathodic modifiers to improve the corrosion resistance of titanium aluminide in all the solutions tested. However, platinum, palladium, and iridium additions shifted the corrosion potentials to the position of the passive region of plain TiAl for all solution concentrations. This indicated that TiAl alloyed with these platinum group metals would passivate spontaneously by cathodic modification. TiAl alloyed with palladium performed the best in 5 wt% HCl solution with the most positive corrosion potential. In 15 wt% HCl solution, alloys with platinum exhibited the most positive corrosion potentials, while alloying with iridium or palladium revealed more negative corrosion potentials. Thus, palladium alloying led to the best cathodic modification of titanium aluminide in low-concentration HCl solution, whereas platinum and iridium alloying additions resulted in the best cathodic modification of titanium aluminide in high-concentration HCl solutions.